The G-Protein-Coupled Bile Acid Receptor Gpbar1 (TGR5) Inhibits Gastric Inflammation Through Antagonizing NF-κB Signaling Pathway - Guo, Cong; Qi, Hui; Yu, Yingjie; Zhang, Qiqi; Su, Jia; Yu, Donna; Huang, Wendong; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Pharmacology, 2015)
Gpbar1 (TGR5), a membrane-bound bile acid receptor, is well known for its roles in regulation of energy homeostasis and glucose metabolism. Here we show that mice lacking TGR5 were much more susceptible to lipopolysaccharide (LPS)-induced acute gastric inflammation than wild-type (WT) mice and TGR5 is a negative regulator of gastric inflammation through antagonizing NF-κB signaling pathway. We found that the treatment of TGR5 ligands 23(S)-mCDCA and GPBARA (3-(2-Chlorophenyl)-N-(4-chlorophenyl)-N,5-dimethylisoxazole-4-carboxamide) suppressed gene and protein expression mediated by NF-κB signaling. TGR5 overexpression with ligand treatment inhibited gene expression of interferon-inducible protein 10 (IP-10), TNF-α, and chemoattractant protein-1 (MCP-1) induced by LPS. Furthermore, we revealed that TGR5 activation antagonized NF-κB signaling pathway through suppressing its transcription activity, the phosphorylation of IκBα and p65 translocation, which suggests that TGR5 antagonizes gastric inflammation at least in part by inhibiting NF-κB signaling. These findings identify TGR5 as a negative mediator of gastric inflammation that may serve as an attractive therapeutic tool for human gastric inflammation and cancer.